write as a single logarithm: -2logbase3(1/x)+(1/3)logbase3(square root of x) please show the steps to solving this. thanx. remember that 1 log (AxB) = log A + Log B (same base) 2 log (A/B) = log A - log B 3 log A^n = n log A use these …
1) use the properties of logarithms to simplify the logarithmic expression. log base 10 (9/300) log - log 300 log 9 = 2 log 3 log 300 = log 3 + log 100 = log 3+2 I just do not know how to put these together now!
Write expression as one logarithm and simplify if appropriate. log 3√x + log x^4 - log x^3 4 log (x+3) - 5 log (x^2+4) + 1/3 log y I have these who problems but I don't know where to start. HELP Please.
The problem I have to solve is log with base 2 ^6 multiply by log base 6 ^ 8. I use the change of base formula and got log6/log2 * log8/log6 Which become log6/log2 * log2()^3/ log 6 I'm stuck here thanks.